Exposure to acid‐suppressing drugs during pregnancy and the risk of asthma in childhood: an observational cohort study. Issue 3 (27th November 2015) - Cea Soriano, L.; Hernández‐Díaz, S.; Johansson, S.; Nagy, P.; García‐Rodríguez, L. A.
Summary: Background: Some research has suggested a potential link between prenatal exposure to proton pump inhibitors (PPIs) or H2 ‐receptor antagonists (H2 RAs) and the development of childhood asthma. Aim: To quantify the relative risk of asthma in children who experienced pre‐natal exposure to PPIs and/or H2 RAs, adjusting for potential confounders. Methods: In this observational cohort study (NCT01787435), women aged 18–45 years with completed pregnancies between January 1996 and December 2010 were identified from The Health Improvement Network in the United Kingdom, and were linked to infants. Hazard ratios (HRs) were estimated using Cox proportional hazard models. Results: Our analysis identified 2371 prenatally exposed and 7745 unexposed infants. The incidence of asthma (per 1000 person‐years) was 19.52 in the unexposed cohort, 23.88 in the PPI cohort and 32.16 in the H2 RA cohort. After adjusting for maternal healthcare utilisation during the year before pregnancy, the HR for asthma in infants whose mothers received prescriptions at any time during pregnancy was 1.12 (95% confidence interval: 0.88–1.44) for PPIs and 1.43 (1.20–1.70) for H2 RAs, when compared with unexposed infants. With further adjustment for maternal comorbidities and other medications, the HR for asthma was 1.03 (0.76–1.40) for PPIs and 1.32 (1.05–1.64) for H2 RAs. Conclusions: Our analysis showed no association between prenatal exposure to PPIs and asthma in childhood after adjusting for confounders. The association found for H2 RAs may be explained largely by underlying environmental or genetic factors, as suggested by reductions in hazard ratio estimates following adjustment for maternal comorbidities.